EXERCISE INTRADIALYSIS TERHADAP PENURUNAN TINGKAT FATIGUE PADA PASIEN HEMODIALISA - Dyah Restuning Prihati; Marisha Dwi Pangesti (Universitas Widya Husada Semarang, 2018)
Chronic kidney failure is that the kidneys are not functioning properly for more than three months. the worst condition of the patient undergoing hemodialysis. Hemodialysis patients experience fatigue conditions namely fatigue, fatigue, lethargy and feelings of energy loss. The purpose of this study was to determine the effect of intradyalysis exercise on fatigue levels in hemodialic patients. Research design with descriptive design and case study method. Sampling uses a nonprobability sampling technique with a purposive sampling approach. The number of 5 respondents who were given intradyalysis exercise. The measuring instrument is the Piper Fatigue Scale (PSF) with 21 items. The results of the study showed that the level of fatigue before physical exercise on average in the category of severe weakness level, with a value of 7.57. While the value of the fatigue level after two physical exercises averaged 3, 87 with a moderate level of weakness. the comparison of fatigue levels before and after the intervention on the first day experienced a decrease in fatigue level of 1.77 while on the second day there was a decrease in fatigue level of 1.71. The conclusion of this study is that intradyalysis exercise can reduce fatigue levels in hemodialysis patients.